DIRECTIVE SPEECH ACTS IN 2 SELECTED EPISODES OF NUSSA ANIMATED SERIES - Fitria, Salsabila (Alphabet, 2023)
The purpose of this study is to find out the types of directive acts in 2 selected episodes of Nussa Animated Series on the YouTube channel entitled "Nussa: Episode Compilation Vol. 7" and "Nussa: Episode Compilation Vol. 7," also the function of the directive used by each character. This research is descriptive qualitative research. The data source for this research is the episodes of the animated series on the Nussa Official YouTube channel. The data of this study were taken from the language used in the conversations in 2 selected Nussa videos. The research findings show five types of directive acts: command, suggest, invite, request, and advise. There are 23 data classified as a command, 2 data classified as suggesting, 4 data classified as inviting, 6 data classified as requests, and 1 data classified as advising in total; This can indicate that the command is the most used directive action by this talk show speaker. This study also shows that directive speech acts in both episodes contain Islamic values and are in line with Islamic speaking procedures.